2019
DOI: 10.1038/s41598-019-51021-2
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated α1-acid glycoprotein as a biomarker to predict prognosis following tumor immunotherapy of patients with lung cancer

Abstract: Immunotherapy targeting immune checkpoint molecules has provided remarkable clinical benefits in cancer patients but no clinically relevant biomarker for predicting treatment outcomes exists. Recently, we demonstrated that glycan structures of serum α1-acid glycoprotein (AGP) changed dramatically in cancer patients and that α1,3fucosylated AGP (fAGP) levels increased along with disease progression and decreased responding to chemotherapy treatments. Here, the fAGP was analyzed in sera prospectively obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
(66 reference statements)
2
22
0
Order By: Relevance
“…A second study, looking at the glycosylation of serotransferrin, reported that biantennary structures containing sialic acid decreased during radiotherapy, and 1 month after finishing the treatment, an abundance of these structures increased, but without reaching the original levels (T oth et al 2016). Glycan related changes that have been identified as markers of inflammation include an increase in the branching of glycan structures in serum proteins (Higai et al 2005) as well as an increase in the levels of sialylation (De Graaf et al 1993;Anthony and Ravetch 2010) and/or fucosylation (Thompson et al 1989;Yokobori et al 2019). Our results, showing an increase in the degree of branching, suggest that inflammation could be a part of the response to chronic exposure to low doses of IR.…”
supporting
confidence: 56%
“…A second study, looking at the glycosylation of serotransferrin, reported that biantennary structures containing sialic acid decreased during radiotherapy, and 1 month after finishing the treatment, an abundance of these structures increased, but without reaching the original levels (T oth et al 2016). Glycan related changes that have been identified as markers of inflammation include an increase in the branching of glycan structures in serum proteins (Higai et al 2005) as well as an increase in the levels of sialylation (De Graaf et al 1993;Anthony and Ravetch 2010) and/or fucosylation (Thompson et al 1989;Yokobori et al 2019). Our results, showing an increase in the degree of branching, suggest that inflammation could be a part of the response to chronic exposure to low doses of IR.…”
supporting
confidence: 56%
“…Glycan structures can change in association with the presence of a tumor or under certain treatment conditions [ 78 , 79 ]. In a small but prospective cohort treated with nivolumab, fucosylated AGP levels appeared a reliable biomarker [ 80 ].…”
Section: Genomics Transcriptomics and Proteomics: Understanding The C...mentioning
confidence: 99%
“…FUT8 gene knockout in mice resulted in a high percentage (up to 70–80 %) of early postnatal death due to the major developmental growth and respiratory defects, while the survivors displayed severe growth retardation and emphysema‐like changes in the lungs [2] . Abnormal expression of cell‐surface core fucosylation has been frequently observed in various cancers such as liver, colorectal, ovarian, prostate, and breast cancer, [3] while the high concentration of core fucose often indicated a poor prognosis and decreased survival [4–6] . Studies indicated that core fucosylation promotes tumor growth, invasion, and metastasis through regulating many cell‐surface growth factors such as epidermal growth factor receptor (EGFR), vascular endothelial growth factor receptor (VEGFR), and transforming growth factor‐β receptor (TGF‐βR) [7–10] .…”
Section: Introductionmentioning
confidence: 99%